Development of Android-based virtual laboratory media at vocational school: effects on students’ cognitive skills - Aisyah Khilawatun Niswah; Roemintoyo Roemintoyo; Triana Rejekiningsih (Institute of Advanced Engineering and Science, 2024)
Vocational school students are not only required to master competency skills but also cognitive skills. Engineering mechanics learning is a basic calculation lesson that students should master. This research aimed to develop and identify the effectiveness of Android-based virtual laboratory (V-lab) media to improve students’ cognitive skills in learning engineering mechanics at vocational school in Surakarta. The subjects comprised 70 students of first grade vocational school majoring in civil engineering in Surakarta. This research was a research and development (R&D) study to develop an Android-based virtual laboratory media. Testing the N-Gain analysis in the experimental and control classes was to determine the effectiveness of virtual laboratory media in improving students’ cognitive thinking skills. Data were obtained from questionnaires and pretest and post-test test sheets. The developed virtual laboratory media was considered ‘very appropriate’ by media, material, and practitioner experts. The average value of N-Gain for the experimental class was 78.19% which was included in the effective category. Meanwhile, in the control class, the average N-Gain value reached 54.07%, which was included in the less effective category. This indicates that the use of Android-based virtual laboratory media for learning is more effective than conventional learning media.